Assessing Character Education in Higher Education: A Qualitative Case Study Utilizing NVivo for Data Analysis - Siregar, Nurliani; Siregar, Hisar (International Journal of Educational Technology and Artificial Intelligence, 2024)
Character education is a fundamental component of higher education, contributing to the holistic development of students and their readiness for ethical decision-making in an increasingly complex world. This study presents a qualitative case study evaluation of character education programs within a university setting. The research employs NVivo, a powerful data processing tool, to analyze and interpret the rich qualitative data collected. By examining the multifaceted dimensions of character education, the study explores its impact, effectiveness, and challenges in its implementation. Findings provide insights into how character education shapes students’ values, behaviors, and ethical perspectives. The study also sheds light on the strategies employed by the university to foster character development. The research findings offer valuable perspectives for higher education institutions committed to cultivating character education as an integral part of their academic mission.